Human‐infecting influenza A (H9N2) virus: A forgotten potential pandemic strain?. (12th January 2020) - Song, Wenjun; Qin, Kun
Abstract: Continuously emergence of human infection with avian influenza A virus poses persistent threat to human health, as illustrated in H5N1, H7N9 and recent surge of H9N2 infections. Long‐term prevalence of H9N2 avian influenza A virus in China and adjacent regions favours the interspecies transmissions from avian to human. Establishment of multiple genotypes of H9N2 variants in this region contributes to the emergence of novel H7N9 and H10N8 viruses which caused human fatalities. Recent increasing human infection with H9N2 virus in China highlights the necessity to closely monitor the interspecies transmission events. Available human H9N2 sequences revealed that Y280/G9 lineage was responsible for the most of human cases. Presence of adaptive mutations beyond the human‐like receptor binding was indicative of the capacity of readily infecting new hosts without prior adaptation. Moreover, enlarged host range of H9N2 virus in this region substantially increased the transmission among mammals. Meanwhile, serological surveys implied human was more susceptible to H9N2 infection, compared with panzootic H5 and H7 subtype avian influenza virus. Thus, control at the source will be the ultimate and effective option for H9N2 pandemic preparedness. This review comprehensively summarized recent updates on H9N2 human infections, aiming to shed light on the prevention strategies against this strain with pandemic potential.